Evaluasi Permukiman Berdasarkan Tingkat Kerawanan Banjir Pada Das Wae Ruhu - Vinka Cilsya Tentua; Ellisa J Gaspersz; Ferad Puturuhu (Universitas Pattimura, 2018)
This study aims to map the level of flood vulnerability and its distribution in the Wae Ruhu watershed, evaluating residential areas that are at different levels of flood vulnerability in the Wae Ruhu watershed. This research was carried out in Wae Ruhu Watershed, Sirimau Subdistrict, Ambon City in August - September 2018. This research was divided into three stages, namely the research preparation stage which included secondary data collection, making land unit maps, fieldwork maps, flood hazard maps. The field research phase includes observing and verifying flood parameters, verifying the extent of flood vulnerability, observing position, density, building construction, and data analysis and reporting stages that produce flood hazard maps and maps of flood-prone residential areas. The results showed that the high vulnerability had an area of ​​60 ha or 3.68%, the medium vulnerability level was 1096 ha or 67.28% and the low vulnerability level was 473 ha or 29.04%. The results of the study also obtained the position of settlements already in the river border even on the banks of the river, the density of settlements were divided into two, namely: 1) densely populated class settlements (99.6%); and 2) infrequent density class settlements (30.5%), and permanent settlement construction , multilevel and not terraced. Keywords: flood, settlement, vulnerability ABSTRAK Penelitian ini bertujuan memetakan tingkat kerawanan banjir dan sebarannya di DAS Wae Ruhu, mengevaluasi wilayah permukiman yang berada pada tingkat kerawanan banjir yang berbeda di DAS Wae Ruhu. Penelitian ini dilaksanakan pada DAS Wae Ruhu Kecamatan Sirimau Kota Ambon pada bulan Agustus – September 2018. Penelitian ini terbagi menjadi tiga tahap yakni tahap persiapan penelitian yang meliputi pengumpulan data sekunder, pembuatan peta satuan lahan, peta kerja lapangan, peta kerawanan banjir. Tahap penelitian lapangan yang meliputi pengamatan dan verifikasi parameter banjir, verifikasi batas tingkat kerawanan banjir, pengamatan posisi, kepadatan, kostruksi bangunan serta tahap analisis data dan pelaporan yang menghasilkan peta tingkat kerawanan banjir dan peta wilayah permukiman rawan banjir. Hasil penelitian diperoleh tingkat kerawanan tinggi memiliki luas 60 ha atau 3,68%, tingkat kerawanan sedang memiliki luas 1096 ha atau 67,28% dan tingkat kerawanan rendah memiliki luas 473 ha atau 29,04%. Hasil penelitian juga di peroleh posisi permukiman sudah berada di sempadan sungai bahkan di bantaran sungai, kepadatan permukiman dibagi atas dua yaitu: 1) permukiman kelas kepadatan padat (99,6%); dan 2) permukiman kelas kepadatan jarang (30,5%), serta konstruksi permukiman permanen, bertingkat dan tidak bertingkat. Kata kunci: banjir, permukiman, tingkat kerawanan